PENGALAMAN PRAKTIK MENGAJAR MAHASISWA PENDIDIKAN SENI PERTUNJUKAN DI SMA PEMBINA PALEMBANG - Afifah Aprisaliani; Syalin Yansa; Kabib Sholeh; Sukardi (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This article describes the teaching practice experiences of Performing Arts Education students during the School Field Introduction Program (PLP) at SMA Pembina Palembang. The study used a descriptive qualitative approach because the main focus was to portray the learning process, not to measure it through numerical data. Data were drawn from school and classroom observations, field notes, photo documentation, and student teachers’ reflections during PLP activities. The findings show that PLP provided direct experience in recognizing the school environment, planning arts learning activities, using learning media, guiding students in class and on the school field, and reflecting on teaching with supervising teachers and lecturers. In performing arts learning, student teachers were required to combine pedagogical skills with demonstrations, clear instructions, expression, movement practice, and classroom management. Students’ responses appeared through attention to media, participation in movement practice, group cooperation, and willingness to perform, although some still needed encouragement and repeated guidance. The article concludes that teaching practice at SMA Pembina Palembang helped student teachers develop pedagogical awareness, creativity, communication, and reflective habits as prospective performing arts teachers.